2013
DOI: 10.15388/informatica.2013.09
|View full text |Cite
|
Sign up to set email alerts
|

Improving Space Localization Properties of the Discrete Wavelet Transform

Abstract: In this paper, a modified version of the discrete wavelet transform (DWT), distinguishing itself with visibly improved space localization properties and noticeably extended potential capabilities, is proposed. The key point of this proposal is the full decorrelation of wavelet coefficients across the lower scales. This proposal can be applied to any DWT of higher orders (Le Gall, Daubechies D4, CDF 9/7, etc.). To open up new areas of practical applicability of the modified DWT, a novel exceptionally fast algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Also, for Haar wavelets, these smaller image blocks do not overlap, whereas for higher order wavelets (Le Gall, Daubechies D4, etc. (Valantinas et al, 2013)) partial overlapping is observed.…”
Section: Partitioning Of the Discrete Wavelet Spectrum Of An Imagementioning
confidence: 93%
“…Also, for Haar wavelets, these smaller image blocks do not overlap, whereas for higher order wavelets (Le Gall, Daubechies D4, etc. (Valantinas et al, 2013)) partial overlapping is observed.…”
Section: Partitioning Of the Discrete Wavelet Spectrum Of An Imagementioning
confidence: 93%
“…The proposed scheme for localizing defects in the defective texture image X def of size NN (N = 2 n , n  N) comprises of four steps, namely: (1) parti-tioning the image X def into non-overlapping image blocks of size , (2) generating HT spectra for the latter blocks, with the use of a computational algorithm (Valantinas et al, 2013)  ; (4) applying the same defect detection "mechanism" to each image block as in the case of the whole test texture image.…”
Section: Localizing Defects In Defective Texture Imagesmentioning
confidence: 99%